Successful Implementation of Newborn Screening for Hemoglobin Disorders in the Philippines - Padilla, Carmencita D. (Int J Neonatal Screen, 2021)
The Philippine newborn bloodspot screening (NBS) program began in 1996 with 24 hospitals and was formalized by legislation in 2004. The NBS panel was recently expanded to include a number of additional hereditary congenital conditions. Expertise and experiences from other NBS programs already screening for hemoglobinopathies were essential to its successful integration into the ongoing dried bloodspot NBS program in the Philippines. Building on clinical experiences and population data from Filipinos born in California, USA, hemoglobinopathies (including thalassemias) were selected for inclusion in the expanded screening panel. Hemoglobinopathy NBS, using high performance liquid chromatography, was implemented in a stepwise manner into the seven regional NBS screening laboratories. A central university laboratory provides confirmatory testing using both capillary electrophoresis and molecular methodologies. NBS results indicating carriers are followed up with educational fact sheets, while results of presumptive disease are referred for confirmatory testing and follow-up with a hematologist. Long-term care is provided through newborn screening continuity clinics across the country. Hemoglobinopathy NBS is now included in the national insurance package and screening uptake continues to increase nationally, exceeding 90% of all newborns in 7400+ hospitals and birthing centers nationwide prior to the COVID-19 pandemic.